KONTRIBUSI PAJAK DAERAH TERHADAT PENDAPATAN ASLI DAERAH (PAD) KOTA KUPANG - Carles Abineno, Boy Boisana; Yewang, Markus U.K (Journal Economic Education, Business and Accounting, 2023)
In order to support equitable development in the country, the government passed decisions on the regions based on Law Number 32 of 2004 concerning regional government and Law Number 33 of 2004 concerning financial balance between the Regional Government and the Central Government. The research was conducted in Kupang City, with reference to seeing the growth of Kupang City Regional income from 2010 to 2014, which continued to increase. This study aims to determine the contribution of regional levies (taxes) to regional income in the city of Kupang. Secondary data-based research with time series data. data collection in this research is based on Documentation Study. The method used in this research is descriptive analysis, the use of this method aims to identify how much regional revenue is received, how big are the various regional levies and how much is the regional levy given to the Regional Revenue of Kupang City from 2011 to 2014. Regional Revenue of Kupang City has experienced improvements and realization always exceed the targets set by the government of the city of Kupang. This is evident from the data on the increase in financial reporting from 2010 to 2014.